2004
DOI: 10.1002/j.1556-6978.2004.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Competencies Specific to Family‐Based Therapy

Abstract: Research has indicated that traditional office‐based family therapy services are not always effective with at‐risk families and that there is an increasing trend toward home‐based delivered services (W. Snyder & E. McCollum, 1999). In this qualitative study, the author explored experienced home‐based family therapists' perceptions of the competencies most salient to the provision of family‐based therapy. Several themes emerged from this study. The author presents 2 central themes: joining—including joining wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Equally important, a home-based counselor practices within a setting that is determined by the client or his or her family (Macchi & O'Conner, 2010;Mosier et al, 2001;Stinchfield, 2004). In turn, a home-based counselor may conduct a session in a setting that includes multiple distractions and safety concerns (Gale & Austin, 2003).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Equally important, a home-based counselor practices within a setting that is determined by the client or his or her family (Macchi & O'Conner, 2010;Mosier et al, 2001;Stinchfield, 2004). In turn, a home-based counselor may conduct a session in a setting that includes multiple distractions and safety concerns (Gale & Austin, 2003).…”
mentioning
confidence: 98%
“…Home-based counseling was created principally as an alternative to out-of-home placement for at-risk youth (Cortes, 2004;Macchi & O'Conner, 2010;Stinchfield, 2004). It gained wide recognition beginning in the 1990s (Hammond & Czyszczon, 2014), and home-based counseling is currently one of the fastest growing segments of mental health services (American Counseling Association [ACA], 2011; U.S. Bureau of Labor Statistics, 2014).…”
mentioning
confidence: 99%
“…Several studies have suggested that a home-based approach has demonstrated reasonable degrees of effectiveness in addressing the following clinical issues: children identified as "seriously emotionally disturbed" or as having a "serious emotional disturbance" (Cherniss and Herzog 1996;Curtis et al 2004;Fuller 2004;Schmidt et al 2006;Sexton and Alexander 2000;Stinchfield 2004;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992); children and adolescents exhibiting antisocial behaviors, juvenile delinquents, and those involved with Juvenile Justice Services (Cherniss and Herzog 1996;Curtis et al 2004;Sexton and Alexander 2000;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992;Zarski and Zygmond 1989); children with autism (Cottrell 1994); children in need of foster care (Fuller 2004); and families more broadly defined as multiproblem, at-risk, or multi-challenged (Adams and Maynard 2000;Cortes 2004;Johnson et al 2002;Schacht et al1989;Slattery and Knapp 2003;Snyder and McCollum 1999;Zarski and Zygmond 1989). Each of these articles has revealed that families involved in HBFT have experienced greater benefits than those who engaged in traditional, office-based treatment approaches.…”
Section: Indications Specific To Hbftmentioning
confidence: 99%
“…For example, the clinician may become more involved with the entire family and community, creating potential boundary issues and anxiety over the clinician's role (Stinchfield, 2004). Additionally, there are distractions in the home, which can make it more difficult to manage sessions (Snyder & McCollum, 1999) and there may be potential safety accessed by following the link in the citation at the bottom of the page.…”
Section: The Purpose Of This Project Was To Develop An Internship Tramentioning
confidence: 99%